Cyclic CO2 – H2O injection and residual trapping: Implications for CO2 injection efficiency and storage security. (January 2019) - Edlmann, K.; Hinchliffe, S.; Heinemann, N.; Johnson, G.; Ennis-King, J.; McDermott, C.I.
Graphical abstract: Highlights: CCS operations at scale will involve periods of changing injection rates. First experimental study into six cycles of water and scCO2 injection. Continuous hysteresis generates cumulative residual trapping and pressure increases. Increased residual trapping increases storage security and efficiency. Increased residual trapping leads to increased injection pressures. Abstract: To meet the Paris Agreement target of limiting global warming to 2 °C or below it is widely accepted that Carbon Capture and Storage (CCS) will have to be deployed at scale. For the first time, experiments have been undertaken over six cycles of water and supercritical CO2 injection using a state of the art high flow rig recreating in-situ conditions of near wellbore injection into analogue storage reservoir rocks. The results show that differential pressure continuously increases over multiple injection cycles. Our interpretation is that multiple cycles of injection result in a reduced effective permeability due to increased residual trapping acting as a barrier to flow resulting in reduced injectivity. This is supported by numerical modelling and field observations that show CO2 injectivity and its variation over time will be affected by multiple cycles of injection. These results suggest that loss of injectivity must be incorporated into the injection strategy and that careful management of cyclic injection will create the opportunity to increase residual trapping.